THE PERFORMANCE OF STATE AND MUNICIPAL PROGRAMS IN THE SYSTEM OF SOCIOECONOMIC DEVELOPMENT OF TERRITORIES - Nikitskaya, Elena; Gorbacheva, Irina; Rusanovsky, Victor; Markov, Vladimir (Revista Inclusiones, 2020)
The basis for the successful funding of any socio-economic project of a territory is its performance. The current practice of assessment of the effectiveness of Russian investment programs, implemented at the state and municipal levels in the process of socio-economic development of territories is considered herein. The main problem of existing methods is the lack of universality; for many areas of funding, individual methods have been developed that complicate their performance assessment. The objective of the study is to propose directions for the improvement of the performance assessment of state and municipal programs in the system of socio-economic development of territories. The existing methods for the performance assessment of the utilization of budget funds at all levels of the budget system are summarized by the authors.